Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2009)
Are you considering writing an article to describe your recent teacher research project? The editorial board at Networks is interested. While we publish discussions of teacher research and accounts of teacher research projects in higher education, we are dedicated to providing a forum for the research and findings of teachers in pre-K through 12 classrooms.